Effects of maize straw biochar application on soil physical properties, morph-physiological attributes, yield and water use efficiency of greenhouse tomato - Zhang, Jie; Liu, Xinna; Wang, Qian (International Journal of Agricultural and Biological Engineering, 2023)
Tomato (Solanum lycopersicum L.) production was threatened by the inefficiency of fertilizers, contributing to the deterioration of the soil environment under greenhouse conditions in southern China. Biochar application could ameliorate the physical properties of soil and enhance the growth and productivity of tomatoes. In this study, a pot experiment was conducted with four biochar addition rates of 0% (BA0), 1% (BA1), 3% (BA3), and 5% (BA5). Results showed that the soil physical properties, morph-physiological indicators, yield, and water use efficiency (WUE) of tomatoes with biochar addition were significantly higher than those of tomatoes without biochar addition. Among the different treatments, BA5 provided the highest total porosity (53.09%), field capacity (40.73%), plant height (72.5 cm), net photosynthetic rate (16.04 mmol/m2·s), total dry matter (184.65 g/plant), yield (54.9 t/hm2), and WUE (38.5 kg/m3). The yield and WUE increased from 44.5 t/hm2 and 31.2 kg/m3 under BA0, respectively, to 54.9 t/hm2 and 38.5 kg/m3 under BA5, respectively. The results suggest that BA5 can maximize improvements in soil physical properties to augment plant growth, thereby increasing the yield and WUE of tomatoes. However, the effects of BA3 and BA5 on WUE were not significantly different. Thus, from the perspective of economic investment, BA3 is recommended. Keywords: maize straw, biochar application, soil properties, water use efficiency, tomato, greenhouse DOI: 10.25165/j.ijabe.20231603.7437 Citation: Zhang J, Liu X H, Wang Q. Effects of maize straw biochar application on soil physical properties, morph-physiological attributes, yield and water use efficiency of greenhouse tomato. Int J Agric & Biol Eng, 2023; 16(3): 151–159.